ТКАЧОВ С. Польсько-український трансфер населення 1944-1946 рр. - Чекаленко, Л. Д. (Український історичний журнал, 1999)
ТКАЧОВ С. Польсько-український трансфер населення 1944-1946 рр. - Тернопіль, 1997. - 206 с.